(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
DIRETOR DA REVISTA Desembargador Federal Antonio Cedenho ASSESSOR Wladimir Rodrigues EQUIPE Lucia Massako Y. C. Rosa Mônica Maria Meloni Sícoli Rafael Leal Ferreira Renata Bataglia Garcia Simone de Alcântara Savazzoni